Comparative Experimental Study of Mortars Incorporating Pumice Powder or Fly Ash - Kizilkanat, Ahmet B.; Oktay, Didem; Kabay, Nihat; Tufekci, M. Mansur (ASCE-AMER SOC CIVIL ENGINEERS, 2016)
The continuous increasing demand and limited availability of artificial pozzolans has led to a search for alternative supplementary cementitious materials such as natural pozzolans. This study was performed to compare the effects of pumice powder and fly ash-blended cement mortars on fresh properties, strength development, drying shrinkage, sulfate resistance, and chloride ion permeability. The experimental study was carried out on seven different paste and mortar mixtures. Mixtures were prepared by replacing 15, 25, and 35% of portland cement with pumice powder and fly ash by weight. Pumice powder adversely affected the consistency of the paste because of its porous and rough structure. On the other hand, the mortars with pumice powder achieved higher strength development and sulfate resistance, lower drying shrinkage, and chloride ion permeability compared to mortars with fly ash. Therefore, pumice powder can be used in producing sustainable, economical, and environmentally friendly cement by reducing the amount of portland cement consumed. (C) 2015 American Society of Civil Engineers.
Keywords: Durability; Fly ash; Fresh properties; Mortar; Pumice powder; Shrinkage; Strength development; GROUND BASALTIC PUMICE; NATURAL POZZOLAN; BLENDED CEMENTS; SULFATE RESISTANCE; SILICA FUME; HIGH-VOLUME; CONCRETE; SLAG; STRENGTH; FINE; Construction & Building Technology; Engineering; Materials Science